The Effect of Soil Management on Pore Size Distribution and Water Infiltration - Wolschick,Neuro Hilton (2021)
Abstract Water infiltration into soil varies significantly with soil type and management practices. Management practices alter soil physical properties, such as porosity and pore size distribution, which play an important role in infiltration. This study was conducted to assess the effect of the long-term use of two different soil tillage systems (conventional, CT, and no-tillage, NT) on soil structure and water infiltration to understanding of the relationship between physical conditions induced by tillage and water infiltration. The experiments were carried out on a Humic Cambisol in southern Brazil from 1995 to 2016. Soil density, porosity, aggregate diameter and soil water infiltration were evaluated under conventional tillage right after one plowing and two subsequent discings (CT0), and six months after these tillage operations (CT6). The results show that different management systems affect differently soil physical properties and, thus, water infiltration. By mechanical mobilization CT brings about modifications in soil structure which promote an increase in total porosity and mesopority, and a decrease in soil microporosity. This in turn results in an increase in the proportion of larger pores in the plow layer and a decrease in soil density, but also in a decrease in aggregate stability. The CT0 measurements showed the highest infiltration rates which were up to 15 times greater than in the NT treatment. The higher infiltration rate in CT0 wears off with time, but in the CT6 measurements six months after tillage it was still 2 times higher than under NT. Tillage, at least initially, increases total porosity and mesoporosity, while at the same time decreasing microporosity. This results in a larger saturated hydraulic conductivity (K). An increase in total porosity alone does not necessarily increase K, if there is an increase in small pores at the cost of decreasing the number of larger pores.